2011
DOI: 10.1002/mawe.201100837
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anodic oxide coating on the fatigue behaviour of AA6082 with an ultrafine‐grained microstructure

Abstract: In this work, the high-cycle fatigue behaviour of the precipitation hardening aluminium wrought alloy AA6082 was investigated for a conventionally-grained and an ultrafine-grained substrate condition, with each a hard and a soft electrolytic anodic oxide (EAO) coating. The investigations were focused on the susceptibility of the coatings to anodising-and fatigueinduced cracking of the coatings and its impact on the fatigue life. For both substrate materials, the fatigue strength of the coated specimens was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…According to previous studies (Hockauf et al, 2011), the crack transition is enhanced for thicker coating layers. Consequently, the coating thickness plays a crucial role for the overall fatigue strength.…”
Section: Sulfuric Acid Anodizingsupporting
confidence: 56%
See 1 more Smart Citation
“…According to previous studies (Hockauf et al, 2011), the crack transition is enhanced for thicker coating layers. Consequently, the coating thickness plays a crucial role for the overall fatigue strength.…”
Section: Sulfuric Acid Anodizingsupporting
confidence: 56%
“…This informs that a greater dispersion of probable values of the fatigue life is expected as the depth of anodizing increases, so that the behavior of the crank is less predictable affecting to the quality and performance of the component. This could be due to the facts observed by Hockauf et al, 2011).…”
Section: Figure 3 Tested Cranks With Different Anodizing Depthmentioning
confidence: 82%
“…The fatigue strength of the MAO coatings decreases compared to the base material since the crack progresses rapidly and results in damage due to the porosity of the MAO structure. In other words, at the endurance limit, the transition of oxide-coated samples to the infinite life zone starts significantly earlier than the uncoated base material due to the inhibition of the cracking onset by the porous oxide layer [6,31]. When the S-N curves of the MAO-epoxy duplex process in Fig.…”
Section: Fatigue Testmentioning
confidence: 98%
“…The effect of anodization on the fatigue strength/life of Al alloys is counted on several process variables. Moreover, the fatigue strength of a soft anodized coating is superior to that of a hard anodized one [ 12 ]. Chromic acid anodizing is less harmful to fatigue strength than sulfuric acid anodizing [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the thickness of the anodizing coating lowers the fatigue strength/life of AA 7075 alloy [ 10 ]. Moreover, a coating on an ultrafine-grained substrate has shown enhanced resistance to anodizing-induced and fatigue-induced cracking of AA 6682 alloy [ 12 ]. It is reported that the microcracks in the anodized film and irregularities beneath the film are the reasons for the decrease in fatigue strength [ 10 ].…”
Section: Introductionmentioning
confidence: 99%